Jak dzisiaj funkcjonuje model młodzieżowej powieści kryminalnej Zbigniewa Nienackiego? O wybranych kontynuacjach powieści o panu Samochodziku = How does Zbigniew Nienacki's model of crime novel for teenagers function today? On the selected novel sequels of "Pan samochodzik" ("Mr. Car") - Borowski, Dominik (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is devoted to the status of the novel "Pan Samochodzik" as written by Zbigniew Nienacki'sfollowers. It opens with a characterisation of detective fiction and youth crime novel as a literarygenres. Then distinguishing features of Nienacki?s novel cycle are discussed, for instance, crime storydiscourse, characterisation of the hero and his opponents, narration, time and place of action. Themain body of the article is devoted to the analysis of the selected continuations of "Pan Samochodzik" by contemporary writers.
Keywords: literatura dla dzieci i młodzieży; Nienacki, Zbigniew (właśc. Nowicki, Zbigniew Tomasz; 1929-1994); powieść kryminalna